Experiential Marketing as Leverage for Growth of Creative Tourism: A Co-creative Process - Ferreira, Jéssica (2019)
Tourism has been playing a very important role as a factor of regional and local development, through the cultural consumption of tourists. Creative tourism emerges from a new paradigm of cultural tourism, where marketing is indispensable in its promotion. Creativity has gained an additional appreciation in fields such as economic, social, political and cultural. The handicraft of Barcelos is recognized for its creativity at any point in the country, representing several activities to promote their own handicraft. The ancient and traditional art of the municipality of Barcelos, with its authenticity and its diversity, transformed its activity into Portugal’s largest handicraft space. This study intends to establish a marketing link with the destination of tourism, making it creative, applied in the handmade artisan offer of the territory of Barcelos. This is a qualitative study, which is intended to do some interviews with various craftsmen, to understand how the offer organizes and how experiential marketing contributes to the growth of the tourism market. At the same time questionnaires are made to several local tourists to understand their motivation in making decisions in the tourist destination of Barcelos. The main findings of this study arise from the experience, knowledge and importance of learning this dynamic. Creative tourism and experiential marketing, more than ever, are growing and strengthening territories, presenting the right moment to establish the connection that this study exposes.